(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2020)
The higher education system in India has constantly strived hard to build colleges and universities as places of culture and learning, keeping them open to everyone and, above all, strengthening the theme of lifelong learning. There are two main research methods, viz. an approach which is quantitative and qualitative. In order to collect data relevant to the research issue and to survey and evaluate the use of e-resources, the level of satisfaction and the requirements experienced by users of university libraries in the north and central regions. The study focuses on legal information resources uses and satisfaction of library services on university of India with special reference to the central and the north.